Definitions of Sexual Dysfunctions in Women and Men: A Consensus Statement From the Fourth International Consultation on Sexual Medicine 2015 - McCabe, Marita P; Sharlip, Ira D; Atalla, Elham; Balon, Richard; Fisher, Alessandra D; Laumann, Edward; Lee, Sun Won; Lewis, Ron; Segraves, Robert T (Journal of sexual medicine, 2016)
Definitions of sexual dysfunctions in women and men are critical in facilitating research and enabling clinicians to communicate accurately. To present the new set of definitions of all forms of sexual dysfunction in women and men adopted by the Fourth International Consultation on Sexual Medicine (ICSM) held in 2015. Classification systems, including the International Classification of Diseases, 10th Edition and the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, and systems that focus on only specific types of sexual dysfunctions (e.g., the International Society for Sexual Medicine definition for premature ejaculation) were reviewed. Evidence-based definitions were retained, gaps in definitions were identified, and outdated definitions were updated or discarded. Where evidence was insufficient or absent, expert opinion was used. Some definitions were self-evident and termed clinical principles. The evidence to support the various classification systems was carefully evaluated. A more comprehensive analysis of this evidence can be found in two other articles in this journal that consider the incidence and prevalence and the risk factors for sexual dysfunction in men and women. These data were used to shape the definitions for sexual dysfunction that have been recommended by the 2015 ICSM. The definitions that have been adopted are those that are most strongly supported by the literature at this time or are considered clinical principles or consensus of experts' opinions. As more research and clinical studies are conducted, there likely will be modifications of at least some definitions.